(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The World Wide Web (or www) has impacted on almost each aspect of our lives. It is the main widely known information source that is easily available and searchable. It consists of billions of interconnected Web pages) which are uploaded and written by millions of people. Web has dramatically changed our information seeking behavior and lifestyle. With the World Wide Web information is only a few clicks away from us. We can find needed information on the Web and also we can easily share information and knowledge with others. The WWW is officially an Internet-based computer network which allows user to access information stored on another computer through the world-wide network called the Internet. This world-wide network follows a standard client-server model. In this model, a client relies on a program on one end and connects to a remote machine called the server where the data is stored. Web browsers like Netscape, Internet Explorer, Firefox work by sending requests to remote servers for information retrieval and interpret the returned documents in HTML in the form of text and graphics on the computer screen on the client side. Hypertext link on a Web Page allows author to link their documents to other related documents residing on computers anyplace in the world. To view these documents, one simply follows the hyperlinks.